2009
DOI: 10.1634/stemcells.2008-0826
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DLK1+ Cells Emerging During Skeletal Muscle Remodeling in Response to Myositis, Myopathies, and Acute Injury

Abstract: Delta like 1 (DLK1) has been proposed to act as a regulator of cell fate determination and is linked to the development of various tissues including skeletal muscle. Herein we further investigated DLK1 expression during skeletal muscle remodeling. Although practically absent in normal adult muscle, DLK1 was upregulated in all human myopathies analyzed, including Duchenne-and Becker muscular dystrophies. Substantial numbers of DLK1 1 satellite cells were observed in normal neonatal and Duchenne muscle, and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 45 publications
(70 reference statements)
10
75
0
Order By: Relevance
“…We used a BAC transgenic model containing the Dlk1 gene within 70 kb of the surrounding sequence and generated three independent transgenic lines (70A, 70B, and 70C) (18). Postnatally, Dlk1 is expressed in the adrenal gland (23), the somatotrophs of the pituitary (24), in a small number of cells in the brain (25), and in stromal-vascular cell populations associated with muscle and adipose tissues (11,26,27). Dlk1-transgenic hemizygous animals (WT/TG) recapitulated this postnatal restriction of Dlk1 expression, ( Fig.…”
Section: Resultsmentioning
confidence: 85%
“…We used a BAC transgenic model containing the Dlk1 gene within 70 kb of the surrounding sequence and generated three independent transgenic lines (70A, 70B, and 70C) (18). Postnatally, Dlk1 is expressed in the adrenal gland (23), the somatotrophs of the pituitary (24), in a small number of cells in the brain (25), and in stromal-vascular cell populations associated with muscle and adipose tissues (11,26,27). Dlk1-transgenic hemizygous animals (WT/TG) recapitulated this postnatal restriction of Dlk1 expression, ( Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Dlk1 has been implicated in skeletal muscle development. It is involved in differentiation of skeletal stem cells (Abdallah et al, 2004) and skeletal muscle remodeling (Andersen et al, 2009). Davis et al (Davis et al, 2004) reported that overexpression of Dlk1 resulted in skeletal muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we used tissue array blocks comprising a panel of normal and abnormal fetal and adult human tissues (kindly provided by Henrik Daa Schrøder, Department of Pathology, Odense University Hospital, Denmark) for further testing of DJ 3, 9, and 18. Immunohistochemical staining was performed as described previously (Andersen et al, 2009), including block of endogenous peroxidase activity and antigen demasking by boiling in TEG buffer [10 mM Tris (SIGMA T-1378)/0.5 mM EGTA (Merck 8435), pH 9.0]. In case of tissue arrays IHC, we blocked endogenous biotin using a biotin-avidin kit system (DAKO A/S, DK), and TEG demasking was performed at 60°C for 24 h to prevent damage of tissues enriched for collagens.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%